Identification and Quantification of Sodium Benzoate in Different Brands of Mango Juices Available in Tangail Region, Bangladesh (Bangladesh Pharmaceutical Journal, 2017)
Chemical preservation has become an increasingly important practice in modern food technology. Sodium benzoate is a permitted food additive in restrictive amounts by international laws, but their content must be declared and must not exceed the established limits by legislation. An experimental study for the level of sodium benzoate in different brands of mango juices available in the markets, stores and shops in Tangail region of Bangladesh was determined by high performance liquid chromatography. A Luna 5 ? C18 (2) 100A column (250 × 4.6 mm) was used for the chromatographic analysis. Chromatographic separation was achieved with isocratic solvent system comprising of sodium acetate and acetic acid buffer (pH =4.0)/acetonitrile in the ratio of 80:20 (1 ml/min) at 37oC and the chromatograms were recorded at 254 nm. The limit of detection and quantification for sodium benzoate was 0.00076 mg/100 ml and 0.00231 mg/100 ml, respectively. Quantification of the selected brand juices revealed that the level of the used sodium benzoate was within the FDA standard range. But by comparing with the Bangladesh Standard and Testing Institute (BSTI), brand-1 and brand-3 of the analyzed juice samples was found to deviate the current legal limits. The percentage recovery was found to be 92.04 ± 1.98 to 98.01 ± 1.91. It was found that some of the brands used excess amount of sodium benzoate which may be harmful for our health.Bangladesh Pharmaceutical Journal 20(1): 20-26, 2017